The safety level of public transportation in Malaysia (Kuala Lumpur) - Ahmad, Siti Naquiah; Aziz, Zulkufli (2012)
Public transport is the main transport for all population to move from one place to another.The main purpose of this study was to analyze the level of passenger safety and improve their safety level to a more satisfying and makes more effective recommendations for a future.This study is doing in Malaysia focused on Kuala Lumpur due to the diversity of public transport.Research methods are using secondary data obtained through a search on the internet, books, journals and articles related to this problem. Information from the search is used to compare and analyze the safety system or security at the terminal or on the route.The findings were obtained from data search is about the levels accident, security and threats.At the end of this study found that the level of safety of public transportation is still less satisfying based on accident statistics and the number of reports on safety made by previous researchers.Recommendations made to further improve the security or safety of passengers.